Evaluation of the graduation profile of pedagogies in the internship process: Measurement from tutor teachers of the school system - Alvarez Barahona, Sandra Eliana; Pizarro Cepeda, Patricia Petronila; Guzmán Loyola, José Miguel (IE Revista de Investigación Educativa de la REDIECH, 2023)
This research is based on the evaluation of the Graduate Profile of pedagogy programs at Universidad de La Serena, during the internship process carried out by students. A quantitative methodology with an exploratory and descriptive approach was used, which allowed knowing the level of achievement of the training provided, incorporating tutors in the measurement of 13 teaching competencies of the graduation profile. Among the findings, it was found that the most descended competencies are teamwork and ITC management, and among the most outstanding are mediator of the teaching-learning process, teaching assertiveness, mastery of content, knowledge of their students and critical thinking. It was also determined that there is no major difference in the performance of students who carried out their internship in the urban or rural sector, nor from types of educational establishments, which indicates that these demographic variables are not determining factors in the level of achievement that students reach. The results constitute resources for the redefinition of future training plans in order to germinate complex reflective processes that include the design of comprehensive, multidimensional and collaborative learning situations, in order to identify elements that hinder and facilitate training.